2022
DOI: 10.1001/jamanetworkopen.2022.13606
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and Infectious SARS-CoV-2 Shedding Kinetics in Vaccinated and Unvaccinated Individuals

Abstract: Key Points Question Do individuals fully vaccinated against COVID-19 have a shorter duration of viable SARS-CoV-2 viral shedding and a lower rate of secondary transmission than in partially vaccinated or unvaccinated individuals? Findings In this cohort study of 173 health care workers, inpatients, and guardians and 45 participants in a community facility, secondary transmission of SARS-CoV-2 was significantly less common, and viable virus was detected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
98
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 16 publications
6
98
1
5
Order By: Relevance
“…All patients were investigated for the number of close contacts during their infectious period (from ≤2 days before symptom onset in symptomatic patients or ≤2 days before the diagnosis day in cases of asymptomatic patients to isolation)(3), and the number of contact individuals who were diagnosed with SARS-CoV-2 infection within 1 week of contact. Definition of close contacts were found in our previous study ( 3 ).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…All patients were investigated for the number of close contacts during their infectious period (from ≤2 days before symptom onset in symptomatic patients or ≤2 days before the diagnosis day in cases of asymptomatic patients to isolation)(3), and the number of contact individuals who were diagnosed with SARS-CoV-2 infection within 1 week of contact. Definition of close contacts were found in our previous study ( 3 ).…”
mentioning
confidence: 76%
“…However, given the low number of fully vaccinated individuals in this study (n=6), we could not detect a significant difference in the duration of viable viral shedding between the two groups that was a different viral shedding kinetic cohort from the cohort for the calculation of the secondary attack rate ( 3 ). Nevertheless, this prospective cohort study builds on our earlier publication ( 3 ) with a different independent cohort involving more fully vaccinated or partially vaccinated and unvaccinated hospitalized patients with COVID-19 at varying degrees of severity. We evaluated the secondary attack rate and viral shedding kinetics in the same cohort and found that fully vaccinated individuals with SARS-CoV-2 infection had lower transmissibility than partially vaccinated or unvaccinated individuals.…”
mentioning
confidence: 83%
See 3 more Smart Citations